Cellular immune activity in response to increased training of elite oarsmen prior to Olympic competition - Jakeman, P. M.; Weller, A.; Warrington, G. (Journal of Sports Sciences, 1995)
This study investigated the changes in urinary neopterin, a biochemical marker of cellular immune activity, in elite male rowers undertaking a progressive increase in training prior to Olympic competition. Twenty-seven male rowers of the 1992 Great Britain team provided daily urine samples for a 4-week period of training that included 17 days of altitude training and 10 days of heat acclimatization. The mean (+/- S.D.) ratio of neopterin/creatinine in urine increased from pre-training values of 135 +/- 32 to a peak of 219 +/- 121 mumol neopterin per mol creatinine on day 19 of training (P < 0.05). Changes in the ratio of neopterin/creatinine with training were found to be transient and highly variable between subjects, ranging from no change to peak values five-fold greater than baseline. On the basis of the in vivo measurement of cell-mediated immunity employed in this study, we conclude that elite athletes engaged in high-intensity training prior to competition show either no change or a moderate increase in cellular immune activation.